A new genus, Perplexacara, and new generic placements of species of Australian marsh beetles (Coleoptera: Scirtidae) based on morphology and molecular genetic data - Watts, C.h.s.; Bradford, T.m.; Cooper, S.j.b. (Zootaxa, 2021)
The Australian Scirtidae species previously identified as misplaced in the widespread genus Prionocyphon Redtenbacher are revisited as well as their possible relationship with the Australian genus Macrodascillus (Lea) using sequence data from the mitochondrial gene, cytochrome oxidase subunit 1 and two nuclear genes, elongation factor 1-alpha and Topoisomerase. The study confirmed the conclusion of Cooper et al. (2014) that the species did not belong in Prionocyphon. The study also included a species from each of three possibly related genera, Chameloscyphon Watts, Daploeuros Watts and Dasyscyphon Watts. Chameloscyphon huonensis Watts, Dasyscyphon victoriaensis Watts and Daploeuros lamingtonensis Watts were recovered as separate lineages with C. huonensis linking with Das. victoriaensis and Dap. lamingtonensis isolated. The species previously included in Prionocyphon were shown to belong in two genera, Macrodascillus and a new genus Perplexacara: Perplexacara caementum (Watts) new combination, P. latusmandibulara (Watts) new combination, P. macroflavida (Watts) new combination, Macrodascillus scalaris (Lea), M. insolitus (Watts) new combination and M. lamingtonensis (Watts) new combination.